Quercetin and Vitamin C: An Experimental, Synergistic Therapy for the Prevention and Treatment of SARS-CoV-2 Related Disease (COVID-19) - Colunga Biancatelli, Ruben Manuel Luciano; Berrill, Max; Catravas, John D.; Marik, Paul E. (Frontiers in Immunology, 2020)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) represent an emergent global threat which is straining worldwide healthcare capacity and it is projected to provoke, between 100.000 and 240.000 deaths in the US. It is absolutely necessary to study and develop pharmacological treatments suitable for the prevention and treatment of SARS-CoV-2 related disease (COVID-19). Ascorbic acid is a crucial vitamin necessary for the correct function of the immune system. It plays a role in the stress response and has shown promising results when administered to the critically ill. Quercetin is a well-known flavonoid whose antiviral properties have been investigated in numerous studies. There is evidence that vitamin C and quercetin co-administration exerts a synergistic antiviral action due to overlapping antiviral and immunomodulative properties and to the capacity of ascorbate to recycle quercetin, increasing its efficacy. Safe, cheap interventions which have a sound biological rationale should be prioritized for experimental use in the current context of a global health pandemic. We present the current evidence for the use of vitamin C and quercetin both for the prophylaxis of the high-risk population and for the treatment of COVID-19 patients.